2022
DOI: 10.3390/jfb13040262
|View full text |Cite
|
Sign up to set email alerts
|

A Development of New Material for 4D Printing and the Material Properties Comparison between the Conventional and Stereolithography Polymerised NVCL Hydrogels

Abstract: The term 4D printing refers to the idea that the shape or properties of a printed object can be changed when an external stimulus is applied. In this contribution, a temperature-responsive polymer Poly (N-vinyl caprolactam) (PNVCL), which is normally prepared via radical free polymerization, was used to justify the 4D printing concept. As a result, by using a Stereolithography (SLA) 3D printer, 4D prints were successfully prepared. These prints were able to demonstrate intelligent and reversible expansion/shri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…As reported in our earlier works [ 18 , 24 ], a hydrogel-based monolayer only displayed volume changes under heating and cooling conversions. In contrast, a simple way of creating monolayer structures that can change their conformations was demonstrated in this contribution.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…As reported in our earlier works [ 18 , 24 ], a hydrogel-based monolayer only displayed volume changes under heating and cooling conversions. In contrast, a simple way of creating monolayer structures that can change their conformations was demonstrated in this contribution.…”
Section: Resultssupporting
confidence: 73%
“…In a previous study, the flower-shaped NVCL-based hydrogels were demonstrated to have excellent swelling capacity, which provided the rationale for the preparation of bilayer structures [ 18 ]. The bilayer flower structure created in this study aims to mimic the flowering process in nature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementation of PNVCL in clinical applications might seem limited presently; however, the tunability of the LCST of PNVCL has been proven practical by recent work [ 41 ]. Our team has also published the effect of applying 3D-printing and UV-curing techniques on fabricating an NVCL-based polymer using two different photoinitiators [ 42 ]. Continuous research on PNVCL will one day all add up to its successful application in numerous areas, including biomedical and shapeshifting areas.…”
Section: Introductionmentioning
confidence: 99%